Relação lazer/trabalho e atitude diante das problemáticas ambientais contemporâneas: desafios para a atuação profissional com o ecoturismo - Cesar Castilho (2017)
This article aims at discussing the performance of professionals that work with ecotourism in the surrounding area of Belo Horizonte and render services in four leisure activities: mountain biking, rock climbing, wildlife viewing and trekking. The investigation was impelled by the following questions: how the work-leisure relation is configured in these professionals’ performance? Which aspects are approached in their discourses and professional performance in relation to the environmental consciousness and environment degradation? The methodology of this qualitative investigation involved bibliographic and field research, in which the data were collected through participant.